Effectiveness of discontinuing antibiotic treatment after three days versus eight days in mild to moderate-severe community acquired pneumonia: randomised, double blind study. Issue 7554 (8th June 2006) - Moussaoui, Rachida el; de Borgie, Corianne A J M; van den Broek, Peterhans; Hustinx, Willem N; Bresser, Paul; van den Berk, Guido E L; Poley, Jan-Werner; van den Berg, Bob; Krouwels, Frans H; Bonten, Marc J M; Weenink, Carla; Bossuyt, Patrick M M; et al.
Abstract: Objective To compare the effectiveness of discontinuing treatment with amoxicillin after three days or eight days in adults admitted to hospital with mild to moderate-severe community acquired pneumonia who substantially improved after an initial three days' treatment. Design Randomised, double blind, placebo controlled non-inferiority trial. Setting Nine secondary and tertiary care hospitals in the Netherlands. Participants Adults with mild to moderate-severe community acquired pneumonia (pneumonia severity index score ≤ 110). Interventions Patients who had substantially improved after three days' treatment with intravenous amoxicillin were randomly assigned to oral amoxicillin (n = 63) or placebo (n = 56) three times daily for five days. Main outcome measures The primary outcome measure was the clinical success rate at day 10. Secondary outcome measures were the clinical success rate at day 28, symptom resolution, radiological success rates at days 10 and 28, and adverse events. Results Baseline characteristics were comparable, with the exception of symptom severity, which was worse in the three day treatment group. In the three day and eight day treatment groups the clinical success rate at day 10 was 93% for both (difference 0.1%, 95% confidence interval − 9% to 10%) and at day 28 was 90% compared with 88% (difference 2.0%, − 9% to 15%). Both groups had similar resolution of symptoms. Radiological success rates were 86% compared with 83% at day 10 (difference 3%, − 10% to 16%) and 86% compared with 79% at day 28 (difference 6%, − 7% to 20%). Six patients (11%) in the placebo group and 13 patients (21%) in the active treatment group reported adverse events (P = 0.1). Conclusions Discontinuing amoxicillin treatment after three days is not inferior to discontinuing it after eight days in adults admitted to hospital with mild to moderate-severe community acquired pneumonia who substantially improved after an initial three days' treatment.